The evaluation of circulating endothelial progenitor cells and related angiogenic markers as prognostic factors in soft-tissue tumors - Karampinis, Ioannis; Joas, Elena; Ronellenfitsch, Ulrich; Jakob, Jens; Hohenberger, Peter; Nowak, Kai (European journal of surgical oncology, 2018)
Introduction - Neovascularisation is a critical step in the progression of malignant tumors. Circulating endothelial progenitor cells (cEPC) have been proposed as surrogate markers of vasculogenesis in malignancies. In this project, we studied the impact of tumor-specific therapy on cEPC and associated angiogenic factors in patients with soft tissue tumors. - Materials and methods - Fifty-three patients with soft tissue tumors (25 soft tissue sarcomas, 19 GIST, 9 desmoids) and 15 healthy controls were included. Blood samples were obtained at two time points, before and 8 weeks after start of tumor-specific therapy. Peripheral blood mononuclear cells (PBMCs) were isolated. cEPCs were characterised as CD34+, CD133+, CD45dim, CD31+ and vascular endothelial growth factor 2 (VEGFR-2) positive cells. Serum concentrations of VEGF-A and angiopoetin-2 were determined by enzyme-linked immunosorbent assay. - Results - VEGF-A and Ang-2 concentrations were significantly higher in tumor patients than in healthy controls in both samples (p < .01). Sarcoma patients with progressive disease developed a significant increase in cEPC levels between the two blood samples compared to those with stable disease (p = .002). GIST patients with progressive tumor or metastatic disease showed significant increase in VEGF-A values (p = .01). - Discussion - The pre-treatment values of the angiogenic markers did not correlate with the clinical course of the disease. However, cEPCs levels were significantly higher in sarcoma patients with progressive disease compared to those with stable disease and should be further evaluated as early markers of disease progression in sarcoma patients. VEGF-A and angiopoetin-2 clearly play a role as mediators of the vasculogenesis contributing to tumor progression.